A four year audit of deliveries by caeserean section at a medical college hospital in Central India - Bharadwaj, Malini; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: There is a global concern for rising rates of deliveries by Caesarean Section over the past few decades. Caesarean deliveries are not only associated with a higher morbidity and mortality but also a longer duration of hospital stay and greater financial burden. Hence they are justified only where better perinatal outcome is expected. An audit of indications of caesarean sections may help identify the areas of intervention for reducing the caesarean delivery rates. Methods: The delivery records were analyzed retrospectively from January 2008 to December 2011. The rates and indications for deliveries by caesarean section were analyzed. Results: The total number of deliveries in the three year period was 4084. Of these, 1965 deliveries were caesarean deliveries (48.1%). Year wise, a rising trend in caesarean section rate was noted: 40.8% in 2008; 46% in 2009; 48.7% in 2010 and 56.5% in 2011. The leading indication for caesarean section was fetal distress (35%). The others major indications were previous caesarean delivery (26%), Cephalo Pelvic Disproportion (10.4%), Malposition/malpresentation (8.2%), prolonged labour (7.8%), Hypertensive disorders of Pregnancy (2.2), Antepartum haemorrhage (2%) and Obstructed labour (1.7%). The proportion of CS done for previous caesarean section steadily increased over the four years and a falling trend was noticed for CS done for prolonged labour. Conclusions: The rate of caesarean section needs to be closely monitored and audited so as to take measures for reducing the caesarean rates. An in depth analysis of caesareans section done for fetal distress and previous CS is recommended so that areas of intervention can be identified. The decision for primary CS should be done after a comprehensive assessment and with due justification.